STRATEGI PEMASARAN LEMBAGA PENDIDIKAN TINGGI: PENDEKATAN KONSEP ISLAMIC MARKETING - Nasukha, Moh; Masyhud, Subaidi (Kopertais Wilayah X Jawa Tengah, 2017)
This research describes the marketing strategy of higher education with model approach of Islamic Marketing concept. To know that customer loyalty has been recognized as an important source to maintain sustainable competition within an institution. Institutions of higher education is one of the organizations that have a level of intense competition. Increased customer loyalty can be done by an institution of higher education to maintain the increasingly tight competition. This paper answers how the strategies undertaken by higher education institutions in mepertahankan competition, through Islamic Markeing concept approach. The results of this study are: customer satisfaction is built on the basis of sharia values, where marketers in serving customers always behave and behave, among others: first gentle, second, generous, and third, customer priority (ÃŽtsÃ¢r).